Comparing the precision of pulse oximetry with finger sensor at finger and ear among Vasopressor-treated patients - mohammad Javad shaban; Ali mohammadpour; mojtaba kianmehr; Tahereh Baloochi Beydokhti (Majallah-i Bālīnī-i Parastārī va Māmāyī, 2018)
Background and aims: Nowadays, finger pulse oximetry has been used for continuous monitoring of oxygen saturation. However, finger pulse oximetry cannot be always applied on fingertips. In such condition, the same sensor of finger pulse oximetry on the ear could be applied for reading the oxygen saturation. Regarding the difference of ear and finger tissues and the fact that finger pulse oximeter has been designed for the finger structure; So, the present study was aimed to determine the precision of finger pulse oximeter when used at finger and ear among the patients who were under Vasopressor treatment. Methods: In this comparative descriptive-analytical study, 33 Vasopressor-treated patients in the intense care ward of Kashmar hospital were were selected based on simple and convenience and entered into the study according to inclusion criteria in 2016. Two finger pulse oximetry sensors were used; one was attached to the fingertip and the other on upper part of auricle. They simultaneously sampled arterial blood. The obtained data were analyzed by SPSS software through Spearman correlation and variance analysis tests on observation replicas. Results: The findings showed that there is a statistically significant difference between SpO2 of the ear (94.03±3.79), fingertip (86.81±4.82) and SaO2 (90.88±3.65) in the Vasopressor-treated patients (P<0.001). Also, there is a statistically significant relationship between oxygen saturation percent and the time of capillary refill. Conclusion: The results of this study demonstrated that in Vasopressor-treated patients, application of finger pulse oximetry on ear would lead to results that are more accurate on oxygen saturation as compared to its application on fingertip.